The Principle of Social Scaling. (18th December 2017) - dos Santos, Paulo L.
Abstract : This paper identifies a general class of economic processes capable of generating the first-moment constraints implicit in the observed cross-sectional distributions of a number of economic variables: processes of social scaling . Across a variety of settings, the outcomes of economic competition reflect the normalization of individual values of certain economic quantities by average or social measures of themselves. The resulting socioreferential processes establish systematic interdependences among individual values of important economic variables, which under certain conditions take the form of emergent first-moment constraints on their distributions. The paper postulates a principle describing this systemic regulation of socially scaled variables and illustrates its empirical purchase by showing how capital- and labor-market competition can give rise to patterns of social scaling that help account for the observed distributions of Tobin's q and wage income. The paper's discussion embodies a distinctive approach to understanding and investigating empirically the relationship between individual agency and structural determinations in complex economic systems and motivates the development of observational foundations for aggregative, macrolevel economic analysis.